2017
DOI: 10.1103/physrevb.95.235435
|View full text |Cite
|
Sign up to set email alerts
|

On-demand source of maximally entangled photon pairs using the biexciton-exciton radiative cascade

Abstract: We perform full time resolved tomographic measurements of the polarization state of pairs of photons emitted during the radiative cascade of the confined biexciton in a semiconductor quantum dot. The biexciton was deterministically initiated using a π-area pulse into the biexciton two-photon absorption resonance. Our measurements demonstrate that the polarization states of the emitted photon pair are maximally entangled. We show that the measured degree of entanglement depends solely on the temporal resolution… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 30 publications
3
45
0
Order By: Relevance
“…Experiments and theoretical studies in semiconductor quantum dots demonstrated the possibility to generate ΦBS entanglement. [ 3,16,29–50 ]…”
Section: Generation Of Entangled Statesmentioning
confidence: 99%
“…Experiments and theoretical studies in semiconductor quantum dots demonstrated the possibility to generate ΦBS entanglement. [ 3,16,29–50 ]…”
Section: Generation Of Entangled Statesmentioning
confidence: 99%
“…Two different QD-microlenses dubbed QDM1 and QDM2 are studied in the following. This excitation scheme has become a well established and powerful technique 5,24,25 , and is nowadays considered as a critical prerequisite for the coherent generation of entangled photons by QDs. We perform these measurements in confocal configuration with a resonant excitation setup.…”
Section: Magdeburg Germanymentioning
confidence: 99%
“…While QDs are interesting objects for studying the fundamentals of the carrier-phonon interaction on the nano-scale, they are likewise highly attractive candidates for applications in quantum information technology. In particular, QDs could be used as single [48][49][50][51][52][53][54][55] or pair photon sources [54,[56][57][58][59][60][61][62][63] or in quantum networks [64]. Therefore it is also of high interest to understand the impact of the carrier-phonon interaction on the properties of the photons emitted from a QD.…”
Section: Introductionmentioning
confidence: 99%